A cross-sectional study of anthropometry and immunization coverage of Anganwadi children in a rural area of Karnataka - Ipsita Debata; T. S. Ranganath; K Josephine Priya; J Tejas (Journal of Family Medicine and Primary Care)
Background: Children are a supreme asset to a nation. Beginning six years of life is pivotal for the social, emotional, cognitive, physical, motor, and psychological upbringing of the child. National Family Health Survey (NFHS) 5 data shows 41.9% of children die before the age of five years, with greater mortality in the rural areas (45.7%). The present study was conducted to assess the anthropometric profile and immunization status of children in Anganwadi centers. Materials and Methods: A community-based cross-sectional study was conducted in 21 Anganwadi centers in a rural area in South India. The anthropometry (height, weight, mid-upper arm circumference), morbidity profile, and immunization status of the enrolled and available children were assessed with the help of WHO growth charts, Salter scale, clinical examination, immunization cards, and data from Anganwadi registers. Statistical analysis: Data were compiled and analyzed using SPSS software version 20. Descriptive data were interpreted as mean and percentages and associations were tested with the Chi-square test, and Fisher’s exact test. A P value of <0.05 was considered to be statistically significant. Results: Around 400 children, aged 0-6 years, participated in the study. The mean age of the study population was 42.08 ± 12.55 months. The overall prevalence of underweight, stunting, and wasting was 52%, 54%, and 47.5% respectively. The most common morbidity was upper respiratory tract infection (11.5%). A majority (97.5%) of children were found to be immunized appropriately as per age. Conclusion: The prevalence of malnutrition was alarmingly high which warrants urgent referral and follow-up. The ICDS services, although substantially beneficial, need focal strengthening with regard to the nutritional status of enrolled children.